The Relationship between Obesity and Hypertension in East Java Province in 2015-2016 - Emira Tasya Ramadhani; Yuly Sulistyorini (Jurnal Berkala Epidemiologi, 2018)
Background: The prevalence of hypertension keeps increasing that remains as a global problem. One of the risk factors for hypertension is obesity. Purpose: This study was aimed to analyze the correlation between hypertension case with obesity case in East Java Province from 2015 to 2016. Methods: The study design was cross-sectional by collecting secondary data of health profile of hypertension case and obesity in East Java. Hypertension was observed in people aged ≥ 18 years old, while the obesity was found in people aged ≥ 15 years old in 38 districts or cities. Data were analyzed through Spearman correlation test. Results: there was a significant correlation between hypertension and obesity (p = 0,01) with the positive direction (coefficient correlation=0.49). By means, the higher hypertension cases found, the higher obesity cases found in East Java Province or vice versa. Conclusion: There was a significant correlation between obesity cases and hypertension cases in East Java Province from 2015 to 2016.